PUSAT ILMU PENGETAHUAN SEBAGAI WAHANA REKREASI EDUKATIF DENGAN PENDEKATAN ARSITEKTUR METAFORA DI SURAKARTA - Clara Afiliati Pritania; Agus Heru Purnomo; Leny Pramesti (ARSITEKTURA, 2016)
Science Center’s planning and designing in Surakarta, motivated by the rapid development of science and technology, the need a place for information and education about science and technology to wider community, the lack of recreation and education facilities about science and technology in Surakarta, and also one of the Surakarta government vision and mission to increase human resources through science and technology. The purpose are to get a building design that can accommodate either recreation and education activities about science and technology, and also the building form which can express the dynamic motion development of science and technology. The issue is how to interpret the dynamic motion of science and technology to the design itself. The methods using architecture metaphor methods. The results are Science Center which applying architecture metaphor intangible (abstract) through building circulation, space system, and the building form.  Keywords: Architecture, Architecture Metaphor, Exhibition Center, Metaphor Intangible,  Science Center, Science and Technology.